Dysbiosis of the Urinary Bladder Microbiome in Cats with Chronic Kidney Disease - Younjung Kim (American Society for Microbiology, 2021)
Despite the clinical importance of urinary diseases in cats, the presence of resident urine microbes has not been demonstrated in cats, and the role of these microbes as a community in urinary health remains unknown. Here, we have shown that cats with and without urinary tract disease harbor unique microbial communities in their urine.